Penerapan Jaminan Asuransi Kesehatan terhadap Perlindungan Pegawai Negeri Sipil (PNS): Studi Pada BPJS Kesehatan Cabang Langkat - Rahimi, Siti; Imsar2,; Syarvina, Wahyu (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Study aims to determine the implementation of health insurance carried out by BPJS Kesehatan, and can be used as a consideration in formulating and designing policies for implementing health insurance for Civil Servants (PNS) and also to find out the obstacles faced by BPJS Kesehatan Langkat Branch. The type of research used is descriptive qualitative research. The conclusions of this study in brief are: (1) The implementation of health insurance at the Langkat Branch of Health BPJS is in accordance with the law on state civil servants that civil servants are entitled to receive pension security, old age security, health insurance, work accident insurance and death security. And the implementation of health insurance for civil servants at BPJS Kesehatan Langkat Branch is in accordance with Law No. 24 of 2011, which stipulates that BPJS Kesehatan functions to organize a health insurance program with the aim of ensuring that participants receive health care benefits and protection in meeting basic health needs. (2) Obstacles found in the Langkat Branch of BPJS Health are delays in service to participants, health facilities obtained are not in accordance with the fees paid, lack of participant data collection. The solution to the obstacles in the Langkat Branch Health BPJS needs to be improved in the service system because what participants need is fast, accurate service and can provide convenience in participant administration. Keywords: Insurance, Health Insurance, Civil Servants, Services, Protection.